Quantitative patterns between plant volatile emissions induced by biotic stresses and the degree of damage - Niinemets, Ülo; Kännaste, Astrid; Copolovici, Lucian (Frontiers in Plant Science, 2013)
Plants have to cope with a plethora of biotic stresses such as herbivory and pathogen attacks throughout their life cycle. The biotic stresses typically trigger rapid emissions of volatile products of lipoxygenase pathway (LOX products, various C6 aldehydes, alcohols and derivatives, also called green leaf volatiles) associated with oxidative burst. Further a variety of defense pathways is activated, leading to induction of synthesis and emission of a complex blend of volatiles, often including methyl salicylate, indole, mono-, homo- and sesquiterpenes. The airborne volatiles are involved in systemic responses leading to elicitation of emissions from non-damaged plant parts. For several abiotic stresses, it has been demonstrated that volatile emissions are quantitatively related to the stress dose. The biotic impacts under natural conditions vary in severity from mild to severe, but it is unclear whether volatile emissions also scale with the severity of biotic stresses in a dose-dependent manner. Furthermore, biotic impacts are typically recurrent, but it is poorly understood how direct stress-triggered and systemic emission responses are silenced during periods intervening sequential stress events. Here we review the information on induced emissions elicited in response to biotic attacks, and argue that biotic stress severity vs. emission rate relationships should follow principally the same dose-response relationships as previously demonstrated for several abiotic stresses. Analysis of several case studies investigating the elicitation of emissions in response to chewing herbivores, aphids, rust fungi, powdery mildew and Botrytis, suggests that induced emissions do respond to stress severity in dose-dependent manner. Bi-phasic emission kinetics of several induced volatiles have been demonstrated in these experiments, suggesting that next to immediate stress-triggered emissions, biotic stress elicited emissions typically have a secondary induction response, possib